Scheduling of Sport League Systems with Inter-League Constraints - Jörn Schönberger (Technische Universität Dresden, Fakultät Verkehrswissenschaften, 2015)
We investigate the simultaneous schedule determination of several leagues in a championship. Beside limited availability of venues, the substitution of players among teams of a club requires the consideration of mutual match slot exclusions associated with teams playing in different leagues during schedule construction. We propose a mathematical optimization model for this complicated decision task and report results from initial computational experiments.
Keywords: 330